PENINGKATAN EFISIENSI PRODUKSI GERABAH DI DESA PENUJAK MELALUI PENGENALAN ALAT AUTOMATIC POTTERY WHEEL DAN ELECTRIC SPRAY GUN - Taqiyyah Ja’izah; Septian Revy Ananda; Sofian Hadi; Aisyia Azzahara; Sartika Sartika; Windi Rohmawati; Widia Widia; Mido Masardi; Ami Muhamad Guntur; Lalu Ardi Marta Wijaya; Saprizal Hadisaputra; Pahrudin Pahrudin; Saprini Hamdiani (Universitas Mataram, 2026)
Penujak Village, located in Central Lombok Regency, is known as the oldest pottery production center on Lombok Island. Supported by skilled and experienced artisans, Penujak pottery is recognized for its high artistic value and serves as a symbol of local cultural identity. However, the production process still relies on manual techniques that are time-consuming, resulting in low productivity, inconsistent shapes, and unstable quality. Therefore, a sustainable development strategy is required. The purpose of this program is to introduce innovations through the use of the Automatic Pottery Wheel and Electric Spray Gun to improve the efficiency, quality, and production consistency without diminishing the artistic and traditional values of Penujak pottery. The activities were carried out through socialization and training sessions aimed at local artisans in Penujak Village. The implementation process consisted of three main stage: socialization, demonstration, and mentoring. The results of the program showed that the introduction of the Automatic Pottery Wheel and Electric Spray Gun had a significant impact on improving the efficiency and quality of pottery production. The time required to produce simple pottery items such as plates, which previously took around ten minutes manually, was reduced to only five minutes using the automatic tool, while maintaining better shape consistency. The Electric Spray Gun also produced more even coloring without covering the distinctive traditional motifs of Penujak pottery. Furthermore, this program successfully increased artisans’ motivation to continue innovating, enhanced product competitiveness, and fostered the growth of the local creative economy in Penujak Village. Thus, the program has successfully achieved its objectives. The Automatic Pottery Wheel proved effective in saving time through stable rotation that accelerates the shaping process, while the Electric Spray Gun produced smoother and more uniform coloring compared to manual methods.